2013
DOI: 10.3402/jev.v2i0.20920
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicle (EV) Array: microarray capturing of exosomes and other extracellular vesicles for multiplexed phenotyping

Abstract: BackgroundExosomes are one of the several types of cell-derived vesicles with a diameter of 30–100 nm. These extracellular vesicles are recognized as potential markers of human diseases such as cancer. However, their use in diagnostic tests requires an objective and high-throughput method to define their phenotype and determine their concentration in biological fluids. To identify circulating as well as cell culture-derived vesicles, the current standard is immunoblotting or a flow cytometrical analysis for sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
211
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(222 citation statements)
references
References 28 publications
10
211
1
Order By: Relevance
“…Moreover, the high centrifugal force used in ultracentrifugation (100,000-200,000 × g) has been shown to cause exosome fusion, promote coagulation, and alter their structures, properties, and functions, which may impact downstream analysis (12,13,18). Other methods, including immunoaffinity capture (19,20), precipitation kits such as ExoQuick (System Biosciences) and Total Exosome Isolation (Invitrogen) (12,21), microfluidics (17,22,23), nanoscale lateral displacement arrays (24), nanostructurebased filtration (25), nanoplasmonic chip (26), magnetoelectrochemical sensor (27), and dialysis membrane filtration (28), have been implemented. However, these methods frequently suffer from drawbacks such as the need for additional reagents/labels, long processing time, low reproducibility, low exosome integrity, low exosome purity, and/or low exosome yield.…”
mentioning
confidence: 99%
“…Moreover, the high centrifugal force used in ultracentrifugation (100,000-200,000 × g) has been shown to cause exosome fusion, promote coagulation, and alter their structures, properties, and functions, which may impact downstream analysis (12,13,18). Other methods, including immunoaffinity capture (19,20), precipitation kits such as ExoQuick (System Biosciences) and Total Exosome Isolation (Invitrogen) (12,21), microfluidics (17,22,23), nanoscale lateral displacement arrays (24), nanostructurebased filtration (25), nanoplasmonic chip (26), magnetoelectrochemical sensor (27), and dialysis membrane filtration (28), have been implemented. However, these methods frequently suffer from drawbacks such as the need for additional reagents/labels, long processing time, low reproducibility, low exosome integrity, low exosome purity, and/or low exosome yield.…”
mentioning
confidence: 99%
“…28 Western blotting analysis for the representative exosomal biomarkers CD63 and CD9 29,30 confirmed that the isolated vesicles were enriched in the exosomal fraction.…”
mentioning
confidence: 82%
“…A recent example applied to EV is the "EV array" [21,22]. The EV array utilizes slides printed with an array of antibodies to capture EV and then determines the amount of captured EV by labeling with a cocktail of biotinylated CD9, CD63 and CD81 and the use of streptavidin-Cy5 as a reporter molecule.…”
Section: C3 Fluorescent Immunosorbent Assay (Flisa)mentioning
confidence: 99%
“…NTA does not detect the concentration of EV, but the concentration of all particles inside the detection size range (typically 80-500 nm [25]). Furthermore, a wide array of reference samples is used, including EV derived from different cell cultures [13,14,16,17,20,21,23,26] and/or plasma [21,27] were used. All these factors lead to considerable uncertainty in the limit of detection.…”
Section: Limit Of Detectionmentioning
confidence: 99%
See 1 more Smart Citation